Effectiveness of systemic treatments for advanced non-clear cell renal cell carcinoma: a systematic review and meta-analysis - Zhang, Yaping; Chen, Jian; Wang, Xiaoyan; Wang, Hui; Chen, Xiaoli; Hong, Jianfeng; Fang, Hongming (Frontiers in Oncology, 2024)
BackgroundNon-clear cell renal cell carcinoma (nccRCC) represents a heterogeneous group of malignancies with substantial differences in morphology, genetic profiles, clinical behavior, and prognosis. Optimal treatment for nccRCC remains unclear, largely extrapolated from evidence available for clear cell renal cell carcinoma (ccRCC). This study aimed to compare the efficacy of current mainstream drug treatments for nccRCC to provide clinical treatment guidance for advanced cases.MethodsWe systematically searched PubMed, Embase, and Cochrane databases for trials published up to January 2, 2024, including controlled and single-arm trials. Primary outcomes included overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS).ResultsWe selected six randomized controlled trials (RCTs) comparing mammalian target of rapamycin inhibitors (mTORi) with vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKIs). These trials included four first-line and two second-line studies, with a total of 398 advanced nccRCC patients. Pooled results showed that VEGFR-TKIs significantly improved PFS compared to mTORi in first-line treatment (relative risk [RR] = 1.387; 95% confidence interval [CI]: 1.04-1.85; p = 0.026). In a single-arm meta-analysis, we included 22 VEGFR-TKI trials, three mTORi trials, 12 immune checkpoint inhibitor (ICI) therapies, five chemotherapy trials, and 10 combination therapy trials. The pooled ORR ranged from 6% (95% CI: 0–16%) to 36% (95% CI: 27–44%), and the pooled DCR ranged from 54% (95% CI: 50–58%) to 81% (95% CI: 70–91%). Subgroup analysis of ICI showed a higher ORR in the PD-L1 positive group compared to the PD-L1 negative group (RR = 3.044; 95% CI: 1.623-5.709; p = 0.001).ConclusionThis systematic review and meta-analysis demonstrate that VEGFR-TKIs improve PFS in first-line treatment compared to mTORi. The single-arm meta-analysis suggest that combination therapies with different mechanisms result in better ORR and DCR. Furthermore, PD-L1 positive patients showed significantly better therapeutic responses with ICI treatment than PD-L1 negative patients.